Effectiveness of ‘Tackle Your Tics’, a brief, intensive group-based exposure therapy programme for children with tic disorders: study protocol of a randomised controlled trial - Danielle Cath; Annet Heijerman-Holtgrefe; Chaim Huyser; Cara Verdellen; Jolande van de Griendt; Laura Beljaars; Kees-Jan Kan; Ramón Lindauer; Pieter Hoekstra; Lisbeth Utens (BMJ Open)
Introduction This paper outlines the study protocol for the Dutch Tackle Your Tics study in youth with tic disorders. Tourette syndrome and chronic tic disorders are prevalent neurodevelopmental disorders, placing considerable burden on youth and their families. Behavioural treatment is the first-line, evidence-based intervention for tic disorders, but tic reduction and availability remain relatively low. Patient associations stress the need for more accessible high-quality treatments, also focusing on improving quality of life. Therefore, the brief, intensive group-based treatment Tackle Your Tics was developed.Methods and analysis Tackle Your Tics is a 4-day intensive and comprehensive group-based intervention for children and adolescents (9–17 years) with Tourette syndrome or a chronic tic disorder. The programme encompasses exposure and response prevention treatment and additional supporting components (coping strategies, relaxation exercises and parent support). To study the effectiveness of Tackle Your Tics and identify predictors/moderators at baseline, a single-blinded randomised controlled trial (n=104) is conducted, comparing Tackle Your Tics (n=52) with a waiting list condition lasting 3 months (n=52). Assessments are performed at similar time points for both groups: at baseline, after 4 weeks, and at 3 and 6 months of follow-up, on tic severity, quality of life and other psychosocial variables.Ethics and dissemination Ethics approval has been obtained from the medical ethical committee of the Amsterdam Medical Centre (METC nr NL66340.018.18, v3 June 2020). Findings will be presented on national and international conferences, peer-reviewed scientific journals, patient organisation meetings and public media. Patient representatives are fully integrated as part of the research team. If Tackle Your Tics proves to be effective, it can expand evidence-based treatment possibilities for children and adolescents with tic disorders. Identifying the psychosocial predictors/moderators for the effectiveness of this intervention can provide personalised treatment advice in the future.Trial registration number NL8052.